Mulberry Leaf Protein: Extraction Technologies, Functional Attributes and Food Applications - Rongxiang Xue; Lichao Chen; Chao Sun; Abrar Muhammad; Yongqi Shao (Foods)
In the context of a rapidly expanding global population, mulberry leaf protein emerges as an emerging source of plant protein, with most applications currently at Technology Readiness Level (TRL), presenting substantial potential for application in functional foods and nutraceuticals. This paper analyzes three key advantages of mulberry leaf protein. Firstly, the abundant and inexpensive production of mulberry leaves establishes a solid foundation for large-scale protein extraction. Secondly, advancements in the preparation processes and production technology for mulberry leaf protein have further enhanced its viability. Thirdly, mulberry leaf protein boasts excellent nutritional value and outstanding functional properties, along with multiple biological activities, including antioxidant effects, aging delay, and blood-pressure-lowering activity. These superior qualities considerably broaden its range of applications. Furthermore, this paper evaluates existing research (before 30 June 2025) while exploring prospective avenues for future investigation. The findings of this review are important for enhancing the understanding of the potential applications of mulberry leaf protein in food science and nutrition. The aim is to provide new ideas for the efficient utilization of mulberry leaf protein resources and the establishment of a global food security system.